Development of a brushless HTS exciter for a 10 kW HTS synchronous generator. (12th January 2016) - Bumby, Chris W; Badcock, Rodney A; Sung, Hae-Jin; Kim, Kwang-Min; Jiang, Zhenan; Pantoja, Andres E; Bernardo, Patrick; Park, Minwon; Buckley, Robert G
Abstract: HTS synchronous generators, in which the rotor coils are wound from high- T c superconducting wire, are exciting attention due to their potential to deliver very high torque and power densities. However, injection of the large DC currents required by the HTS rotor coils presents a technical challenge. In this paper we discuss the development of a brushless HTS exciter which operates across the cryostat wall to inject a superconducting DC current into the rotor coil circuit. This approach fundamentally alters the thermal load upon the cryogenic system by removing the need for thermally inefficient normal-conducting current leads. We report results from an experimental laboratory device and show that it operates as a constant voltage source with an effective internal resistance. We then discuss the design of a prototype HTS-PM exciter based on our experimental device, and describe its integration with a demonstration HTS generator. This 200 RPM, 10 kW synchronous generator comprises eight double pancake HTS rotor coils which are operated at 30 K, and are energised to 1.5 T field through the injection of 85 A per pole. We show how this excitation can be achieved using an HTS-PM exciter consisting of 12 stator poles of 12 mm YBCO coated-conductor wire and an external permanent magnet rotor. We demonstrate that such an exciter can excite the rotor windings of this generator without forming a thermal-bridge across the cryostat wall. Finally, we provide estimates of the thermal load imposed by our prototype HTS-PM exciter on the rotor cryostat. We show that duty cycle operation of the device ensures that this heat load can be minimised, and that it is substantially lower than that of equivalently-rated conventional current leads.